Farmer and Adviser Perspectives on Business Planning and Control in Mediterranean Agriculture: Evidence from Argolida, Greece - Iakovidis, Dimitrios; Gadanakis, Yiorgos; Park, Julian (My University, 2023)
Adoption and implementation of business planning and control methods is essential to efficiently and effectively allocate resources for producing food within sustainable agricultural systems in the Mediterranean Basin. To investigate this issue, an analysis of twenty-eight representative farming businesses from the National Farm Accountancy Data (FADN) for the region of Argolida (Greece) was undertaken, together with a survey of twenty agricultural advisers (ten agronomists and ten accountants) from the representative associations of agronomists and accountants for the area under study. Results demonstrate farmers’ needs for enhancing managerial competencies, particularly the systematic use of planning and control methods, for effective decision making and strategic design. The research illustrates how these methods can serve as a tool to enhance efforts towards a more sustainable approach to farming. Advisers are encouraged to diversify their role from a purely market driven approach to a role which includes guidance and scientific advice for supporting the sector’s needs for sustainable development. This will support farmers’ decision-making based on the latest scientific knowledge and use of available data to enhance the sustainability of these important agricultural systems.
Keywords: business planning and control; decision-making; decision support tools; arm sustainability; Mediterranean